TES DAN PENGUKURAN ATLET BOLA TANGAN KOTA MAKASSAR PERSIAPAN EKSEBISI SULAWESI SELATAN 2022 - Achmad Karim; Muhammad Akbar Syafruddin; Ikadarny Ikadarny; Wa Ode Sindir (KORSAcs: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service activity is to improve the quality and quantity of knowledge and technology by utilizing proven scientific methods and theories. In the development of sports coaching to improve achievement, many factors must be taken as a form of coaching. One of the factors in the development of sports Coaching is the science in the field of sports which is commonly called sport science. Lack of coach's understanding of test measurement as an evaluation material for athlete development. This condition became the focus of the team in providing an understanding of tests and measurements in handball. The method of implementation is a test to measure the physical condition and technique of athletes in the sport of handball. The results of the Makassar City handball athlete mentoring training are the results of measurement tests in the form of athlete data along with a description of the recommendations related to the data results.